Staphylococcus aureus Temperate Bacteriophage: Carriage and Horizontal Gene Transfer is Lineage Associated - Mccarthy, Alex J.; Witney, Adam A.; Lindsay, Jodi A. (Frontiers in Cellular and Infection Microbiology, 2012)
Staphylococcus aureus is a major cause of human and animal infections. Bacteriophage are a class of mobile genetic element (MGE) that carry virulence genes and disseminate them horizontally, including Panton-Valentine Leukocidin (PVL), the immune evasion cluster (IEC) associated with human specificity, and enterotoxin A the major toxin associated with food poisoning. S. aureus isolates group into major clonal complex (CC) lineages that largely evolve independently due to possession of different restriction-modification (R-M) systems. We aimed to better understand the horizontal and vertical transmission dynamics of virulence and resistance genes by bacteriophage by using (i) bioinformatic approaches to analyse bacteriophage genomes from the first 79 sequenced S. aureus isolates and (ii) S. aureus microarrays to analyse the distribution of bacteriophage and virulence genes in S. aureus isolates from a broader range of lineages. The distribution of eight bacteriophage families was highly variable but lineage associated. Nevertheless, there was evidence of frequent acquisition and loss and not just vertical transmission. Most bacteriophage genes were dispensable, and extensive mosaicism was seen. Surprisingly, virulence genes were tightly associated with specific phage families. This data suggests S. aureus bacteriophage evolve rapidly, and the horizontal gene transfer (HGT) of virulence genes encoded by bacteriophage is restricted by bacteriophage family and the lineage of the host bacterium, delaying the evolution of fully resistant and virulent strains.